Duodenal and retroperitoneal hematoma after upper gastrointestinal endoscopy: First presentation of a child with Hemophilia B - M. Osman; C. Mantor; J. O'Connor (Elsevier, 2014)
Duodenal hematoma is an uncommon complication after upper gastrointestinal endoscopy. Most reported cases resolve with conservative management for 3-4 weeks. The authors report a case of a 7 year-old child who developed duodenal and retroperitoneal hematomas, as well as intra-peritoneal hemorrhage after a diagnostic upper gastrointestinal endoscopy. Surprisingly, this was the patient's first presentation of his later-diagnosed Hemophilia B. This is the first Case report of duodenal hematoma after upper endoscopy as the only first presentation of a coagulation disorder. The case report also describes successful management of such complication.